Correction: Large-scale sensor systems based on graphene electrolyte-gated field-effect transistors. Issue 2 (3rd January 2018) - Mackin, Charles; Palacios, Tomás
Abstract : Correction for 'Large-scale sensor systems based on graphene electrolyte-gated field-effect transistors' by Charles Mackin, et al., Analyst, 2016, 141, 2704–2711.